Factor H, membrane cofactor protein, and factor I mutations in patients with hemolysis, elevated liver enzymes, and low platelet count syndrome - Fakhouri, Fadi; Jablonski, Mathieu; Lepercq, Jacques; Blouin, Jacques; Benachi, Alexandra; Hourmant, Maryvonne; Pirson, Yves; Dürrbach, Antoine; Grünfeld, Jean-Pierre; Knebelmann, Bertrand; Frémeaux-Bacchi, Véronique (Blood, 2008)
The HELLP syndrome, defined by the existence of hemolysis, elevated liver enzymes, and low platelet count, is a serious complication of pregnancy-related hypertensive disorders and shares several clinical and biologic features with thrombotic microangiopathy (TMA). Several recent studies have clearly shown that an abnormal control of the complement alternative pathway is a major risk for the occurrence of a peculiar type of TMA involving mainly the kidney. The aim of this study was to screen for complement abnormalities in 11 patients with HELLP syndrome and renal involvement. We identified 4 patients with a mutation in one of the genes coding for proteins involved in the regulation of the alternative pathway of complement. Our results suggest that an abnormal control of the complement alternative pathway is a risk factor for the occurrence of HELLP syndrome.